The risk of use small matrices to measure specialization in host–parasite interaction networks: a comment to Rivera-García et al. (2016). Issue 8 (31st March 2017) - LUNA, PEDRO; CORRO, ERICK J.; AHUATZIN-FLORES, DIANA A.; ANTONIAZZI, REUBER L.; BARROZO, NATHALIA; CHÁVEZ-GONZÁLEZ, EDGAR; MORALES-TREJO, JUAN J.; DÁTTILO, WESLEY
SUMMARY: In the last years, there were a growing number of studies using the metric H 2 ′ to calculate complementary specialization in host–parasite interaction networks. However, only a few studies have explored the sensitivity of H 2 ′ to network dimensions (i.e. species richness and number of interactions), which consequently could generate studies that are not comparable among them or lead to biased conclusions. In this study, we used the recent published study conducted by Rivera-García et al . in 2016 involving host–bat fly networks as an example to call attention to the risk of using H 2 ′ to calculate specialization for small matrices. After conducting analyses based on both empirical and simulated data, we show that H 2 ′ values are strongly affected by randomly allocation of species interactions to another cell in the matrix for small networks and that therefore the results and conclusions presented in Rivera-García et al . in 2016 are only an artefact of the dataset used. Therefore, we fully recommended taking into account the careful use of small networks to measuring specialization in host–parasite interactions.